Augmenting retail reality. part a, - Verma, Balraj; Mittal, Amit; Raman, Murali; Sindhav, Birud (Emerald Publishing Limited, 2024)
In an era marked by unprecedented technological advancements, the retail industry is at the forefront of a transformative journey. 'Augmenting Retail Reality, Part A: Blockchain, AR, VR, and the Internet of Things' delves into the dynamic interplay between cutting-edge technologies and the evolving landscape of retail commerce. This book serves as a comprehensive guide for retailers, researchers, students, and technology enthusiasts, exploring how innovations such as the Internet of Things (IoT), blockchain, robotics, Augmented Reality (AR), Virtual Reality (VR), and other emerging technologies are reshaping the retail sector. The genesis of this book is rooted in the recognition that technology is not merely an auxiliary component but a fundamental driver of change in retail. As the digital revolution continues to accelerate, retailers must navigate a complex and rapidly evolving environment where customer expectations are constantly shifting, and new opportunities for growth are continually emerging. This publication is a response to the urgent need for an in-depth examination of how these technologies are transforming customer experiences, operational efficiencies, and business models within the retail industry.
Includes index.
Keywords: Chain stores.; Internet of things -- Economic aspects.; Augmented reality -- Economic aspects.; Computers -- Electronic Commerce.; Business innovation.; E-commerce: business aspects.; elektronické knihy; electronic books